2019
DOI: 10.1111/jsr.12865
|View full text |Cite
|
Sign up to set email alerts
|

The effects of sleep extension on cardiometabolic risk factors: A systematic review

Abstract: Summary Studies have shown bidirectional relationships between short‐ or long‐sleep duration and risk for obesity, non‐communicable diseases, all‐cause mortality and cardiovascular disease mortality. Increasing sleep duration may be an appropriate strategy to reduce cardiometabolic risk in short‐sleeping individuals. The aim is to review the effects of sleep extension interventions on cardiometabolic risk in adults. The PubMed and Scopus databases were searched for relevant, English, peer‐reviewed scientific p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 70 publications
(149 reference statements)
1
22
1
Order By: Relevance
“…Although previous studies have shown that recent sleep history (e.g., banking sleep, sleep extension) affects subsequent neurobehavioral responses to sleep restriction [50][51][52], we did not observe differences in caloric and macronutrient intake responses between participants randomized to receive one, three, or five nights of recovery sleep between exposures. In a previous study [21], we noted that intake responses to sleep restriction were linked to hours of additional wakefulness rather than recent sleep history.…”
Section: Discussioncontrasting
confidence: 93%
“…Although previous studies have shown that recent sleep history (e.g., banking sleep, sleep extension) affects subsequent neurobehavioral responses to sleep restriction [50][51][52], we did not observe differences in caloric and macronutrient intake responses between participants randomized to receive one, three, or five nights of recovery sleep between exposures. In a previous study [21], we noted that intake responses to sleep restriction were linked to hours of additional wakefulness rather than recent sleep history.…”
Section: Discussioncontrasting
confidence: 93%
“…With regard to non-respiratory sleep disorders, a systematic review of the effects of prolonged sleep time on cardiometabolic risk factors [74] included only three small-scale studies in which BP was evaluated. None of these reported a significant positive effect.…”
Section: Other Sleep Disordersmentioning
confidence: 99%
“…Interestingly, the superiority of the Mediterranean lifestyle intervention in increasing HDLC and reducing the risk of MS was evident regardless of percent weight change, suggesting that regular physical activity and optimal sleep habits can have additional benefits for the cardiometabolic health of OSA patients, on top of weight loss achieved through a healthy dietary pattern, and should therefore be part of lifestyle interventions for the management of OSA. A reasonable explanation is the well-established beneficial effect of physical activity on body composition, HDLC levels and insulin sensitivity [42], as well as the beneficial effect of an adequate sleep duration and good quality sleep on glucose metabolism [43].…”
Section: Discussionmentioning
confidence: 99%